POPULATION ATTRIBUTABLE FRACTIONS OF CARDIOVASCULAR BURDEN ASSOCIATED WITH ABDOMINAL OBESITY IN CHINA-BASED A NATIONAL SURVEY. (April 2021) - Kang, Yuting; Wang, Zengwu; Chen, Zuo; Zhang, Liinfeng; Wang, Xin; Zheng, Congyi; Jiang, Linlin; Shao, Lan; Tian, Ye
Abstract : Objective: To provide updated and accurate provincial estimates of the burden of cardiovascular diseases attributable to abdominal obesity and to estimate the geography heterogeneity on cardiovascular diseases (CVD) burden. Design and method: The multivariable-adjusted RRs by cox regression using cohort study with more than 30, 000 individuals, along with the national BP level from national study, were used to calculate the population attributable fractions (PAF). China Hypertension Survey, involving 458, 273 participants from 262 selected counties by stratified multistage random sampling method was used to calculate the prevalence of abdominal obesity. CVD events were defined as the incidence of fatal and non-fatal stroke, fatal and non-fatal coronary heart disease (CHD), heart failure, and other causes from CVD. Results: Of more than 30, 000 individuals aged 35 years or older in the current study, over a mean of 143, 314.6 person-years years of follow up, we documented 571 cardiovascular events. Nationally, the CVD events attributable to abdominal obesity was 34.85%. The PAFs for abdominal obesity ranged from 16.86% in Tianjin to 4.21% in Hainan. In 2016, about 420.95 thousand (95%CI: 410.68–431.65) cardiovascular deaths were derived from abdominal obesity, with PAF of 10.95%. The provinces with high socio-demographic Index (SDI), such as Shanghai, Beijing and Tianjin, all had relative lower CVD death numbers for hypertension. Conclusions: Abdominal obesity were related with excess CVD deaths. Geography heterogeneity exited among 31 provinces, with lower excess CVD deaths in high SDI provinces.